A prospective study on pattern of superficial surgical site infections in patients undergoing emergency laparotomy for perforation peritonitis - Singh, Mayank; Agarwal, Ratika; Singh, Rahul (International Surgery Journal, 2020)
Background: surgical site infections (SSIs) are recognized as a common surgical complication occurring in about 3% of all surgical procedures and in upto 20% of patients undergoing emergency intraabdominal procedures. Aims: To determine the incidence of SSIs in emergency laparotomies done for perforation peritonitis and the organisms involved and their sensitivity pattern in superficial SSI. The objective of the study was to determine the effect of planned intra operative intervention [antibiotic lavage with III generation cephalosporin e.g. ceftriaxone 1 gm and metronidazole 100 ml (5 mg per ml)] on superficial surgical site infection in emergency laparotomies done for perforation peritonitis. Methods: This prospective randomized case controlled study was carried out in P. G. Department of Surgery, S. R. N. Hospital associated with M. L. N. Medical College, Allahabad, from September 2018 to August 2019 after approval from the ethical committee and after obtaining written and informed consent either from patient or their guardian. Patients were divided into two groups viz. control group receiving the normal saline lavage and case group receiving the antibiotic lavage (III generation cephalosporins i.e., ceftriaxone (1 gm in 1000 ml NS) and metronidazole- 5 mg/ml (100 ml in 500 ml NS). Results: There is almost 50% incidence of SSI in emergency laparotomy done for perforation peritonitis. The most common organism involved in superficial SSI in present study was gut flora (E. coli) followed by normal skin colonizer (Staph. aureus). Conclusions: Intraperitoneal antibiotic lavage has a significant role in reducing the rate of SSI especially in gastroduodenal perforations.